Ultrathin Magnetic 2D Single‐Crystal CrSe. Issue 19 (28th March 2019) - Zhang, Yu; Chu, Junwei; Yin, Lei; Shifa, Tofik Ahmed; Cheng, Zhongzhou; Cheng, Ruiqing; Wang, Feng; Wen, Yao; Zhan, Xueying; Wang, Zhenxing; He, Jun
Abstract: 2D magnetic materials have generated an enormous amount of attention due to their unique 2D‐limited magnetism and their potential applications in spintronic devices. Recently, most of this research has focused on 2D van der Waals layered magnetic materials exfoliated from the bulk with random size and thicknesses. Controllable growth of these materials is still a great challenge. In contrast, 2D nonlayered magnetic materials have rarely been investigated, not especially regarding their preparation. Cr n X (X = S, Se and Te; 0 < n < 1), a class of nonlayered transition metal dichalcogenides, has rapidly attracted extensive attention due to its abundance of structural compounds and unique magnetic properties. Herein, the controlled synthesis of ultrathin CrSe crystals, with grain size reaching the sub‐millimeter scale, on mica substrates via an ambient pressure chemical vapor deposition (CVD) method is demonstrated. A continuous CrSe film can also be achieved via precise control of the key growth parameters. Importantly, the CVD‐grown 2D CrSe crystals possess obvious ferromagnetic properties at temperatures below 280 K, which has not been observed experimentally before. This work broadens the scope of the CVD growth of 2D magnetic materials and highlights their significant application possibilities in spintronics. Abstract : The synthesis of ultrathin nonlayered CrSe single crystals with a lateral size of up to ≈150 μm and a thickness as low as ≈2.5 nm is realized. The CrSe flakes exhibit obvious ferromagnetic properties. This work not only paves the way for the synthesis of 2D magnetic materials but also has applications in spintronics.